OPTIMALISASI KEGIATAN PRAPEMBELAJARAN DALAM PENCIPTAAN SUASANA RELIGIUS - Junaidi Junaidi; Taufiqur Rahman (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
Research that had done in SMA Ibrahimy Wongsorejo has the aim to describe comprehensively pre-learning activities in creating a religious scene. This research using qualitative research methodology and data collection technique by observation, interview, documentation. The data was analyzed by data reduction, display, as well as taking the result and verification technique. This research on pre-learning activities in creating a religious scene produced several findings are get used to reading Alquran, pray Dhuha, read the surah Yaasin and sholawat Nariyah. Besides that, the impact of pre-learning activities in creating a religious scene in SMA Ibrahimy Wongsorejo has made a calm and conducive learning environment, polite and courteous character of the student and academic community, increasing confidence and trust in the power of prayers and holy Quran, as triggers for student achievement.